Implementasi Pengabdian Masyarakat melalui Pelaksanaan Dirasah Islamiyah di Desa Tukamasea Kabupaten Maros - Munawara Munawara; Iskandar Iskandar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
The village of Tukamasea is one of the villages that has become a post for the placement of class III STIBA Makassar students in the Bantimurung District, Maros Regency. The implementation of community service scheduled by KKN STIBA Makassar students aims to facilitate the development of the quality of understanding of Muslim Muslim religion in Tukamasea Village, Bantimurung District, Maros Regency. Through the implementation of Islamic dirose which is manifested through various Islamic education and teaching programs for Muslim women. Through community service programs implemented in various dirosa Islamiyah activities for Muslim women in Tukamasea Village, it can be concluded that most of the Muslim women in Tukamasea Village before joining the dirosah Islamiyah program have knowledge and understanding of Islam. which is minimal and after participating in dirosah islamic activities, Muslim women in Tukamasea Village have an increase in knowledge and understanding of Islam.